The Existence of Street Vendors in Business: Opportunities and Challenges - Sufa, Amanda Oktavia; Zainarti, Zainarti; Anggraini, Tuti (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
This study aims to explain how street vendors survive and the obstacles they face amid modern business competition triggered by retail expansion and the shift to online commerce. The research uses a descriptive qualitative approach in one of the markets in Indonesia, with four main informants who are traders of various commodities (casual clothing, baby and children's clothing, foodstuffs, and fruits), supplemented by brief confirmation from market managers and customers. Data was obtained through stall observation, in-depth interviews, and document review; analyzed thematically and mapped into a framework of strengths, weaknesses, opportunities, and threats. The findings reveal five most consistent strategies: strengthening services that foster trust; maintaining quality while organizing merchandise displays; starting to utilize simple digital channels (messaging and cashless payments based on Bank Indonesia's standard QR code); improving operational efficiency (stock and cost management); and collaborating with suppliers and the local community. The main obstacles include uneven digital literacy, limited capital and facilities, price pressure from modern retailers, and uncertainty regarding business space. The practical implications are the need for concise digital and managerial assistance, access to microfinance for small value-added improvements, and participatory market structuring. This article contributes by translating cross-commodity daily strategies into an action plan that is easy for traders and stakeholders to adopt.